Trajectories of prostate-specific antigen after treatment for prostate cancer. (22nd November 2017) - Wu, Ziyue; Aslan, Mihaela; Lin, Haiqun; Ko, John; Radhakrishnan, Krishnan; Wells, Carolyn K; Uchio, Edward; Concato, John
Abstract : Prostate-specific antigen (PSA) measurements after primary treatment reflect residual tumor burden among men with prostate cancer. Using a mixture model analysis, we identified distinct trajectories of post-treatment PSA measurements and evaluated their associations with prostate cancer mortality. The study sample included 623 US Veterans treated for prostate cancer with curative intent during 1991–1995; 225 men received surgery and 398 men received radiation therapy. Post-treatment PSA measurements over a 2-year period for each patient were evaluated in latent class mixture models using the SAS TRAJ procedure, and groups of men with distinct trajectories of PSA were identified. These groups were then assessed for associations with 10-year prostate cancer mortality using proportional hazards analysis. Analyses identified three distinct groups—representing patterns of both initial values and changes in PSA over time—after surgery (n=172/31/14) and radiation therapy (n=253/103/22). Men in groups with patterns of higher (compared with the group with lowest) PSA values tended to have worse survival experience: HRs for prostate cancer mortality were 3.45 (P=0.18) and 22.7 (P<0.001) for surgery, and 2.70 (P=0.005) and 18.1 (P<0.001) for radiation therapy. The results indicate that PSA measurements after surgery or radiation therapy with curative intent include groups of men with a diverse spectrum of prognosis for prostate cancer mortality. Although contemporary PSA levels are lower than those observed in the study sample, the corresponding trajectory patterns may become evident shortly after the time of diagnosis and treatment.